Responsiveness of the anterior cruciate ligament - Return to Sports after Injury (ACL-RSI) and Injury - Psychological Readiness to Return to Sport (I-PRRS) scales - Slagers, A. J.; van den Akker-Scheek, I.; Geertzen, J. H. B.; Zwerver, J.; Reininga, I. H. F. (Journal of Sports Sciences, 2019)
The ACL-Return to Sport after Injury (ACL-RSI) and Injury-Psychological Readiness to Return to Sport (I-PRRS) scales were developed to assess psychological factors associated with return to sports. Validity and reliability have been determined. The aim of this study was to investigate the responsiveness of the Dutch ACL-RSI and I-PRRS. Seventy patients with ACL reconstruction completed both scales twice 2 months apart, plus a Global Rating of Change (GRC) questionnaire. Distribution and logistic regression-based methods were used to study responsiveness. The Standardized Response Mean (SRM) for the ACL-RSI was 0.3 and for the I-PRRS 0.1, indicating low responsiveness. The minimally important change (MIC) for ACL-RSI was 2.6 and for the I-PRRS 0.9. Since the standard error of measurement (SEM) and smallest detectable change (SDC) were larger than MIC in individual patients, it does not seem possible to distinguish minimally important changes from measurement error in individual patients with either scale. At the group level responsiveness seemed sufficient; hence, both scales can be used to investigate the effectiveness of an intervention at the group level. Both scales can also be used in cross-sectional research and in clinical practice as screening instruments to identify patients at risk of not returning to sports.